Influence of Nicotine Metabolism Ratio on [(11)C]-(+)-PHNO PET Binding in Tobacco Smokers - Di Ciano, Patricia (Int J Neuropsychopharmacol, 2018)
BACKGROUND: Identifying the biological basis of smoking cessation success is of growing interest. The rate of nicotine metabolism, measured by the nicotine metabolite ratio, affects multiple aspects of nicotine dependence. Fast nicotine metabolizers tend to smoke more, experience more withdrawal and craving, and have lower cessation rates compared with slow metabolizers. The nicotine metabolite ratio predicts treatment response, and differences in brain activation between fast metabolizers and slow metabolizers have been reported in fMRI studies. As reinforcing/rewarding effects of tobacco are associated with dopamine transmission, the purpose of the present study was to study the dopaminergic system in human smokers based on their nicotine metabolite ratio. METHODS: The first aim of the study was to explore if there were differences in D(2) and D(3) receptor binding between fast metabolizers and slow metabolizers during abstinence. The second aim was to explore smoking-induced dopamine release in both groups. Participants underwent 2 [(11)C]-(+)-PHNO PET scans: one scan during abstinence and the other after smoking a tobacco cigarette. Subjective measures were recorded and blood was drawn for measurement of nicotine and cotinine levels. RESULTS: During abstinence, slow metabolizers (n = 13) had lower [(11)C]-(+)-PHNO binding potential than fast metabolizers (n = 15) restricted to the D(2) regions of the associative striatum and sensorimotor striatum. After smoking a cigarette, [(11)C]-(+)-PHNO binding potential was decreased in the limbic striatum and ventral pallidum, suggestive of increases in dopamine, but there were no nicotine metabolite ratio differences. CONCLUSIONS: Further studies are required to delineate if differences in [(11)C]-(+)-PHNO binding between slow metabolizers and fast metabolizers at abstinence baseline are preexisting traits or induced by prolonged tobacco use.